Impact of land cover on air pollution at different spatial scales in the vicinity of metropolitan areas. (December 2021) - Huang, Dian; He, Bing; Wei, Lai; Sun, Liqun; Li, Yangzhong; Yan, Zengxiang; Wang, Xiaoxue; Chen, Yuanlei; Li, Qinglan; Feng, Shengzhong
Highlights: The intra-region air pollutant variations are even greater than inter-region/season differences. Cropland is more important in causing air pollution at regional scales, while the impervious surface mainly impacts at local scales. Cropland acts as the source of NO2 in the north and sink of NO2 in the south. The relationship between extreme O3 levels and LC shows increased variations across seasons from south to north. Abstract: China's urbanization process is accompanied by land use and cover change (LUCC), influencing variations of air pollutants at multiple spatial scales. Monitoring the spatiotemporal variations of air pollutants and their relationship with land cover (LC) is vital for understanding the mechanisms of land-air interaction and guiding environmental management. In this study, both statistical and geo-statistical analysis is used to investigate the relationship between spatiotemporal variations of air pollutants and LC composition in the vicinity of China's three major urban agglomerations (UAs), including Jing-Jin-Ji (JJJ), Yangtze River Delta Region (YRD), and Guangdong-Hong Kong-Macau Greater Bay Area (GBA). Results show that the spatial variations of six criteria air pollutants intra-region are large, even greater than inter-region and inter-season differences. Partial correlation analysis shows that although the impervious surface is the main driving force in elevating air pollution on a local scale, cropland is more important in elevating air pollutant levels at a regional scale. Besides that, the relationship between air pollutant levels and LC demonstrates varied seasonal and regional characteristics for different air pollutants. Our analysis provides a comprehensive understanding of the relationship between air pollutant levels and LC composition, emphasizing the impact of LC at different spatial scales.